LEGAL REVIEW OF INFRINGEMENT PROSECUTION UNDER GOVERNMENT REGULATION OF INDONESIA NO. 80/2012 THROUGH TELEGRAM LETTER OF THE HEAD OF INDONESIAN NATIONAL POLICE NO. ST/2264/X/HUM.3.4.5./2022 - Putra, Erki Maulana; Sholehuddin, Dr. M. (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2023)
The issuance of the telegram letter of the Head of Indonesian National Police No. ST/2264/X/HUM.3.4.5/2022, on 18 October 2022, has an impact on traffic law enforcement. The letter prohibits police officers from manually ticketing traffic violators. After the issuance of the letter, there was a norm conflict with Government Regulation No. 80/2012. This research aims to determine the legal authority between policies and regulations and legal protection for police officers who are proven to use the manual ticketing system after the issuance of the National Police Chief's telegram letter. This research is a normative legal research, which is a type of research that examines documents with various secondary data such as court decisions, legal theories, laws, and regulations. The findings of this research indicate that the Government Regulation has a higher position than the Chief of Police's telegram letter. Therefore, members of the Indonesian National Police who are still detected conducting manual ticketing can obtain legal protection because National Police Chief Regulation No. 14/2011 explains that every member of Indonesian National Police who is a subordinate is obliged to refuse superior orders that are contrary to legal norms.